Heart rate kinetics during standard cardiopulmonary exercise testing in heart transplant recipients: a longitudinal study. (8th January 2021) - Schumacher, Oliver; Trachsel, Lukas D.; Herzig, David; Mohacsi, Paul; Sigurdardottir, Vilborg; Wilhelm, Matthias; Eser, Prisca
Abstract: Aims: Heart transplantation (HTx) results in complete autonomic denervation of the donor heart, causing resting tachycardia and abnormal heart rate (HR) responses to exercise. We determined the time course of suggestive cardiac reinnervation post HTx and investigated its clinical significance. Methods and results: Heart rate kinetics during standard cardiopulmonary exercise testing at 2.5–5 years after HTx was assessed in 58 patients. According to their HR increase 30 s after exercise onset, HTx recipients were classified as denervated (slow responders: <5 beats per minute [b.p.m.]) or potentially reinnervated (fast responders: ≥5 b.p.m.). Additionally, in 30 patients, longitudinal changes of maximal oxygen consumption and HR kinetics were assessed during the first 15 post‐operative years. At 2.5–5 years post HTx, 38% of our study population was potentially reinnervated. Fast responders were significantly younger (41 ± 15 years) than slow responders (53 ± 13 years, P = 0.003) but did not differ with regard to donor age, immunosuppressive regime, cardiovascular risk factors, endomyocardial biopsy, or vasculopathy parameters. While HR reserve (56 ± 20 vs. 39 ± 15 b.p.m., P = 0.002) and HR recovery after 60 s (15 ± 11 vs. 5 ± 6 b.p.m., P < 0.001) were greater in fast responders, resting HR, peak HR of predicted, and peak oxygen consumption of predicted were comparable. Conclusions: Signs of reinnervation occurred mainly in younger patients. Maximal oxygen consumption was independent of HR kinetics.